2002
DOI: 10.1203/00006450-200212000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Increases Sleep and Brain Allopregnanolone Concentrations in Newborn Lambs

Abstract: Infection has been identified as a risk factor for sudden infant death syndrome (SIDS). Synthesis of allopregnanolone, a neuroactive steroid with potent sedative properties, is increased in response to stress. In this study, we investigated the effect of endotoxin (lipopolysaccharide, LPS) on brain and plasma allopregnanolone concentrations and behavior in newborn lambs. LPS was given intravenously (0.7 g/kg) at 12 and 15 d of age (n ϭ 7), and resulted in a biphasic febrile response (p Ͻ 0.001), hypoglycemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 33 publications
2
21
1
Order By: Relevance
“…The rise in AP concentrations following the asphyxia challenge is consistent with our previous finding of responses to hypoxic stress in newborn lambs (Billiards et al 2002) and of others of responses to stress in adult animals (Barbaccia et al 1996). We previously found that lambs of 10–26 days postnatal age subjected to 2 h of hypoxia displayed a dramatic elevation in brain AP content within 1 h (Billiards et al 2002), while 1 min of CO 2 inhalation in adult rats has been shown to cause an increase in AP within 30 min in the brain (Barbaccia et al 1994). Furthermore, brain and spinal cord injury has also been shown to result in the accumulation of neurosteroids, including AP around the focal point of injury (Di Michele et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rise in AP concentrations following the asphyxia challenge is consistent with our previous finding of responses to hypoxic stress in newborn lambs (Billiards et al 2002) and of others of responses to stress in adult animals (Barbaccia et al 1996). We previously found that lambs of 10–26 days postnatal age subjected to 2 h of hypoxia displayed a dramatic elevation in brain AP content within 1 h (Billiards et al 2002), while 1 min of CO 2 inhalation in adult rats has been shown to cause an increase in AP within 30 min in the brain (Barbaccia et al 1994). Furthermore, brain and spinal cord injury has also been shown to result in the accumulation of neurosteroids, including AP around the focal point of injury (Di Michele et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The finding that plasma AP and one of its important precursors, pregnenolone, did not change following UCO, in contrast to the changes seen in the brain extracellular fluid, supports the contention that mechanisms within the brain are primarily responsible for the rise in AP concentrations following UCO. Our previous findings with neonates (Billiards et al 2002) and in the fetus (Nguyen et al 2004) suggest that adrenal synthesis contributes to plasma AP concentrations. The present observations suggest that these mechanisms do not contribute to the changes seen immediately after an asphyxial challenge.…”
Section: Discussionmentioning
confidence: 75%
“…Progesterone can attenuate microglial activation, microgliosis, astrogliosis, and can suppress cytokine release (Labombarda et al, 2011; Munroe, 1971; Robinson & Klein, 2012). Unlike progesterone, AlloP is a potent, positive allosteric modulator of GABA A receptors (Majewska et al, 1986; Paul & Purdy, 1992), a potential negative allosteric modulator of NMDA receptors (Johansson & Le Grevès, 2005; Maurice et al, 2006), is produced in response to immune challenge (Billiards et al, 2002; Ghezzi et al, 2000), and can reduce excitotoxicity partly through rapid increases of tonic inhibition in models of CNS insult (Baulieu & Schumacher, 2000; Brunton et al, 2014; Mellon et al, 2008; Sayeed & Stein, 2009). Allopregnanolone is produced rapidly in response to stress challenges to restore sympathetic and parasympathetic tone (Barbaccia et al, 1996; Patchev et al, 1994, 1996), functions which are observed to be dysregulated among some HIV + individuals (Chittiprol et al, 2007, 2008; Hurwitz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma was treated with 1% acetic acid and 50% methanol and homogenised before being added to Sep‐Pak 18 cartridges. The extracts were treated 5% in potassium permanganate in water to reduce cross‐reactivity of progesterone in samples, before re‐extraction with 50%v/v diethyl‐ether/n‐hexane (Billiards et al, 2002). Concentrations of allopregnanolone were quantified using polyclonal antibody to allopregnanolone (Agrisera, Sapphire Bioscience, Vannas, Sweden), and tritium‐labelled allopregnanolone tracer (5α‐[9,11, 12, 3 H(N)]; PerkinElmer Life and Analytical Sciences, Boston, MA, USA) as previously described (Bennett et al, 2015).…”
Section: Methodsmentioning
confidence: 99%